Kenya under colonial rule, in Government reports, 1907-1964. - Great Britain. Foreign and Commonwealth Office (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2016)
The colony of Kenya was managed by the government departments who wrote these A1:F79 reports. They start when Kenya was a part of the East Africa Colony and continue until independence. The statistics for Kenya are included in Colonial Africa in official statistics, 1821-1953. These reports explain why those statistics are at the levels recorded. The contents pages at the front of each report list the departments which existed at that time. Comparing the contents pages reveals how the structure of the colonial government changed over time.
Date range: 1907-1964.
Keywords: Kenya -- Politics and government -- To 1963.